Improving Lagrangean Decomposition: Some Theoretical Results - Bárcia, Paulo (2019)
Recently two new ways of obtaining improved Lagrangean bounds have been suggested: Variable splitting/ Lagrangean decomposition and bound improving sequences. The aim of this work is to obtain a Lagrangean approach combining the two ideas mentioned above. We provide some theoretical results about the sharpness of the bounds obtained by the combined approach. We show that they dominate the bounds obtained by any of the two individual techniques.